HOW TO RECOGNIZE WHICH LEARNING STYLE A STUDENT NEEDS - Gulbakhor Tursunboyeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Students are the unique entities with different characteristics to be paid attention by the teachers in teaching and learning process. Teachers can feed their students based on their unique characteristics. Students learning style is one of the entities which will contribute toward students’ success in learning. This paper is aimed to identify and to prepare information about students’ major perceptual learning style preferences and to identify and to prepare information about students’ minor learning preferences.